Preparation method of copper-platinum bimetallic nitrogen-doped biochar nano material and prepared material
Copper-platinum bimetallic nitrogen-doped biochar nanomaterials were prepared by using biochar nanomaterial support, oxygen functionalization and nitrogen doping treatment in fuel cell electrode catalyst, and the existing catalysts were solved The problems of high cost and low performance have achieved efficient and low-cost catalytic performance improvement.
Patent Information
- Application Number
- CN202411600173.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing fuel cell electrode catalysts are costly to prepare and the catalytic performance of non-precious metal catalysts is low, making it difficult to meet the dual challenges of cost-effectiveness and performance requirements.
Using biochar nanomaterials as support, oxygen functionalization is functionalized by sulfuric acid and nitric acid, and nitrogen is calcined in an ammonia atmosphere, and then copper-platinum sol is synthesized under microwave heating and loaded onto nitrogen-doped carbon nanopowder. , copper-platinum bimetallic nitrogen-doped biochar nanomaterial was prepared.
The catalytic activity of the oxygen reduction of the catalyst is improved, the preparation cost is reduced, and waste reuse and environmental protection are achieved by utilizing biomass resources.
Smart Images

Figure CN119447341A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fuel cells, and in particular to a method for preparing a copper-platinum bimetallic nitrogen-doped biochar nanomaterial from biomass that can be used as a fuel cell electrode catalyst, and the prepared material. Background Art
[0002] The electrocatalyst performance of the fuel cell electrode determines the performance of the electrode, which in turn affects the performance of the entire fuel cell. Carbon-supported platinum is a commonly used electrocatalyst with good performance, but platinum is a precious metal and the production cost of the catalyst is relatively high. In order to reduce costs, people partially replace platinum with metals such as Cu, Ru, Sn, Co, and Ni, which can reduce costs, but the catalytic performance will also be reduced accordingly. Therefore, how to improve the preparation methods of these catalysts and improve the catalytic performance of non-precious metal catalysts is an important problem to be solved in this field.
[0003] Traditional activated carbon materials are derived from petroleum and coal chemical products, which are resource-limited and have high preparation costs. Biochar is derived from waste biomass and is renewable, cheap, and environmentally friendly. Most waste biomass will have a significantly increased surface roughness after high-temperature carbonization, and has attracted much attention as a biochar raw material for preparing electrochemical related materials. Corn is a common crop in my country, and corn stalks are an underutilized byproduct. Using biomass as a catalyst carbon substrate in fuel cell catalysts can not only achieve the reuse of straw waste, but also solve the environmental and economic problems caused by straw waste. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a copper-platinum bimetallic nitrogen-doped biochar nanomaterial. The biochar carrier prepared by the method is derived from biomass corn stalks, and the synthesized catalyst nanomaterial is used as an electrode catalyst for a fuel cell, has good catalytic performance, and has a relatively low preparation cost.
[0005] In view of the above process, the present invention adopts the following technical solutions: A method for preparing bimetallic nitrogen-doped biochar nanomaterials, characterized by comprising the following steps: Step S1: reacting biochar nanomaterials with sulfuric acid and nitric acid to obtain oxygen-functionalized nanopowders, and then calcining the oxygen-functionalized nanopowders at 400° C. in an ammonia atmosphere to obtain nitrogen-doped nanopowders; Step S2: dissolving chloroplatinic acid and cupric chloride in ethylene glycol to obtain a first solution, wherein the molar ratio of copper to platinum is 5:3 to 3:5; dissolving alkali metal hydroxide in ethylene glycol to obtain a second solution; mixing the first solution and the second solution and heating them in a microwave under an inert atmosphere for 1 minute to obtain a copper-platinum sol, wherein the microwave power is 1000 W; Step S3: dissolving the copper-platinum sol in ethanol, and then adding the nitrogen-doped nanopowder in an amount that ensures that the theoretical loading rate of copper-platinum in the nitrogen-doped nanopowder is 20-25%, and then adding nitric acid, standing by ultrasound, and then centrifuging to obtain a solid, and drying and grinding the solid to obtain a copper-platinum bimetallic nitrogen-doped biochar nanomaterial.
[0006] Preferably, the concentration of chloroplatinic acid in the first solution is 0.01-1.00 g / mL.
[0007] Preferably, the alkali metal hydroxide is sodium hydroxide or potassium hydroxide.
[0008] Preferably, the biochar nanomaterial is prepared by the following method: crushing corn stalks into 80-100 meshes, sieving, and drying in an oven at 80°C for 24 hours; carbonizing the dried stalk particles at 800°C for 3 hours under N2 protection to obtain the biochar nanomaterial.
[0009] Another object of the present invention is to provide a bimetallic nitrogen-doped biochar nanomaterial prepared by the above method.
[0010] The present invention has the following beneficial effects: firstly, the biochar nanomaterial is oxygen-functionalized by mixed acid treatment to form C=O or CO on its surface, and nitrogen-doped by NH3 to successfully incorporate nitrogen-containing functional groups such as pyrrole and pyridine; then, a microwave-assisted polyol reduction method is used to successfully prepare a platinum-copper nanoalloy sol, and ethylene glycol is oxidized to carboxylic acid during the reaction, and acts as a protective agent; finally, the platinum-copper nanoalloy is loaded onto nitrogen-doped carbon nanopowder, and the metal particles have good dispersion. The prepared catalysts all show a certain oxygen reduction catalytic activity, and the oxygen reduction catalytic activity of the four catalysts is CuPt-NCM3:5>CuPt-NCM1:1>CuPt-NCM5:3>Pt-NCM. As the proportion of metal Cu increases, the catalytic oxidation-reduction reaction (ORR) activity tends to decrease. Because the copper content increases, more oxides are generated, which are not conducive to the nucleation of Pt elements and affect the structure of platinum-copper alloys. In addition, too many metal oxides may cover the surface of the alloy structure, unable to expose enough catalytic active sites, affecting the ORR activity of the catalyst. Calculations show that at 0.7 V, the mass activity of the CuPt-NCM3:5 catalyst is 1.2 times that of the commercial Pt / C catalyst, and its kinetic activity is 1.12 times that of the commercial Pt / C catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 XRD spectra of nitrogen-doped biochar nanomaterials loaded with metal catalysts prepared in Example 1 and Comparative Example 1.
[0012] Figure 2The UV-visible spectra of cupric chloride ethylene glycol solution without heating and microwave heating for 50s.
[0013] Figure 3 This is the UV-visible spectrum of chloroplatinic acid ethylene glycol solution under microwave heating.
[0014] Figure 4 This is the infrared spectrum of platinum-copper alloy biochar nanomaterial.
[0015] Figure 5 Pt-NCM(a), CuPt-NCM 3:5 (b), CuPt-NCM 1:1 (c), CuPt-NCM 5:3 (d) SEM and EDX images.
[0016] Figure 6 CuPt-NCM 3:5 Mapping diagram and SEM image of C, O, N, Pt and Cu elements of the catalyst.
[0017] Figure 7 Pt-NCM, CuPt-NCM 3:5 , CuPt-NCM 1:1 , CuPt-NCM 5:3 XPS full spectrum.
[0018] Figure 8 For the sample CuPt-NCM 3:5 XPS spectra of C1s, O1s, and N1s.
[0019] Fig. 9 XPS spectra of Pt4f and Cu2p of each catalyst.
[0020] Fig.10 Pt-NCM(a), CuPt-NCM 3:5 (b), CuPt-NCM 1:1 (c), CuPt-NCM 5:3 (d) HRTEM image.
[0021] Fig.11 Pt-NCM(a), CuPt-NCM 3:5 (b), CuPt-NCM 1:1 (c), CuPt-NCM 5:3 (d) Metal particle size distribution diagram.
[0022] Fig.12 Pt / C (a), Pt-NCM (b), CuPt-NCM3:5 (c), CuPt-NCM 1:1 (d), CuPt-NCM 5:3 (e) Cyclic voltammogram of the 20th cycle.
[0023] Fig.13 CuPt-NCM 1:1 Cyclic voltammetry curves at different scan periods.
[0024] Fig.14 CuPt-NCM 3:5 Cyclic voltammetry curves at different scan rates.
[0025] Fig.15 Pt / C (a), Pt-NCM (b), CuPt-NCM 3:5 (c), CuPt-NCM 1:1 (d), CuPt-NCM 5:3 (e) Linear sweep voltammogram.
[0026] Fig.16 Linear sweep voltammograms of different catalysts in O2-saturated 0.5 mol / L sulfuric acid electrolyte at a scan rate of 5 mV / s, a rotation speed of 1600 rpm, and room temperature.
[0027] Fig.17 CuPt-NCM 3:5 (a) and KL curves of Pt / C (b).
[0028] Fig.18 Electrochemical surface area diagram of different catalysts.
[0029] Fig.19 Mass activity diagrams of different catalysts at 0.675 V and 0.7 V: Pt / C (a), Pt-NCM (b), CuPt-NCM 3:5 (c), CuPt-NCM 1:1 (d), CuPt-NCM 5:3 (e).
[0030] Fig. 20 Comparison of Tafel plots and kinetic activities of different catalysts. DETAILED DESCRIPTION
[0031] 1. Preparation and Characterization Example 1 Preparation of Copper-Platinum Bimetallic Nitrogen-Doped Nanomaterials Step 1: Use mixed acid to modify the surface of nanomaterials to functionalize their oxygen groups, thereby increasing the active sites on the surface of the material, making it easier to effectively combine with metals, and then perform nitrogen doping. The specific operations are as follows: The corn stalks were crushed into 80-100 meshes, sieved, and placed in an oven to dry at 80°C for 24 hours; the dried stalk particles were carbonized at 800°C for 3 hours under N2 protection to obtain biomass nanomaterial powder.
[0032] Weigh 6.0 g of carbon nanopowder into a 500 mL three-necked flask, then add 216 mL of concentrated sulfuric acid, 72 mL of deionized water, and 72 mL of concentrated nitric acid in sequence and mix them. Then heat the oil bath to 100 °C, react for 4 hours, and let it cool overnight. Use a dropper to absorb the acidic substances on the surface of the cooled solution, rinse with deionized water 3-4 times, and then filter. Wash the filtered solid with ethanol twice, put it in a 120 °C oven and dry it for 4 hours to obtain oxygen-functionalized carbon nanopowder. Place the oxygen-functionalized carbon nanopowder in a tubular resistance furnace and heat it to 400 °C. Purge the oxygen-functionalized carbon nanopowder with ammonia for 8 hours to obtain nitrogen-doped carbon nanopowder.
[0033] Step 2: Use microwave heating to prepare copper-platinum sol. Microwave heating is fast and uniform, which can control the shorter nucleation and crystallization time, generate smaller metal particles, improve particle dispersion, and the local high temperature generated by rapid heating enhances the reduction rate of metal ions. The specific operation is as follows: 2 mL of 0.02 g / mL chloroplatinic acid ethylene glycol solution was respectively transferred into three beakers, and 20 mL of ethylene glycol reducing agent was added into each beaker. Then, 0.0088 g, 0.0264 g and 0.0792 g of cupric chloride dihydrate were added into the three beakers in the molar ratio of Cu to Pt of 3:5, 1:1 and 5:3, respectively. Then, the three beakers were placed in an ultrasonic cleaner and ultrasonicated for 15 minutes to obtain the first solution.
[0034] Take three more beakers and place them in the same order as the metal atoms copper and platinum and the hydroxide ions OH - The weight ratio of the mixture is 1:50, 0.40 g, 0.60 g and 1.20 g of sodium hydroxide are added, and then 25 mL of ethylene glycol is added respectively, and ultrasonication is performed until dissolved to obtain a second solution.
[0035] The second solution was added to the first solution in the above order, and after stabilization for 20 min, poured into a 100 mL round-bottom flask and moved into a microwave reactor. The round-bottom flask was connected to an external reflux device through the through hole on the top of the microwave reactor. Argon was introduced into the round-bottom flask for 10 min, maintaining a gas flow rate of 60 mL / min, and then the microwave power of the microwave reactor was set to 1000 W and heated for 1 min to obtain a copper-platinum sol.
[0036] Step 3: Pour the platinum copper sol into three 100 mL beakers and add ethanol to 80 mL, then add 0.0502 g, 0.0598 g, and 0.0892 g of nitrogen-doped carbon nanopowders, respectively, to ensure that the theoretical metal loading rate is 25 wt%, add appropriate amount of nitric acid, adjust the pH to 6-8, ultrasonicate for 20 min, and let stand overnight. Then pour out the supernatant, wash with ethanol 3-4 times, and separate the remaining part with a centrifuge at a speed of 9000 rpm for 5 min. After centrifugation, pour out the supernatant, retain the solid, place the centrifuge tube in a vacuum drying oven, set the pressure to -100 kPa, the temperature to 100 ℃, and the time to 12 h. Grind the three dried catalysts into powder to obtain copper-platinum bimetallic nitrogen-doped biochar nanopowders, labeled as CuPt-NCM 3:5 、CuPt-NCM 1:1 、CuPt-NCM 5:3 .
[0037] Comparative Example 1 Preparation of platinum-nitrogen doped carbon nanopowder Step 1: Same as Example 1, that is, weigh 6.0 g of carbon nanopowder and put it into a 500 mL three-necked flask, then add 216 mL of concentrated sulfuric acid, 72 mL of deionized water, and 72 mL of concentrated nitric acid in sequence and mix them. Then heat to 100 ° C, react for 4 hours, and let stand to cool overnight. Use a dropper to absorb the acidic substances on the surface of the cooled solution, rinse with deionized water 3-4 times, and then filter. Wash the filtered solid with ethanol twice, put it in a 120 ° C oven and dry it for 4 hours to obtain oxygen-functionalized carbon nanopowder. Place the oxygen-functionalized carbon nanopowder in a tubular resistance furnace and heat it to 400 ° C, purge the oxygen-functionalized carbon nanopowder with ammonia for 6 hours to obtain nitrogen-doped biochar nanomaterials.
[0038] Step 2: Prepare platinum sol by microwave heating method. The specific operation is as follows: 2 mL of 0.02 g / mL chloroplatinic acid ethylene glycol solution was respectively transferred into beakers, and 20 mL of ethylene glycol reducing agent was added into beakers. The beakers were placed into an ultrasonic cleaner and ultrasonicated for 15 min to obtain a first solution.
[0039] Take another beaker and add the metal atom platinum and hydroxide ion OH - 0.15 g of sodium hydroxide was added in a weight ratio of 1:50, and then 25 mL of ethylene glycol was added, and ultrasonication was performed until dissolved to obtain a second solution.
[0040] The second solution was added to the first solution, and after stabilization for 20 min, it was moved into a microwave reactor and argon was introduced for 10 min, maintaining the gas flow rate at 60 mL / min. Then, the microwave power of the microwave reactor was set to 1000 W and heated for 1 min to obtain a platinum sol.
[0041] Step 3: Pour the platinum sol into a 100 mL beaker and add ethanol to 80 mL, add 0.0452 g of nitrogen-doped biochar nanopowder respectively, ensure that the theoretical loading rate of the metal is 25 wt%, add appropriate amount of nitric acid, adjust the pH to 6-8, ultrasonicate for 20 minutes, and let stand overnight. Then pour out the supernatant, wash with ethanol 3-4 times, and separate the remaining part with a centrifuge at a speed of 9000 rpm for 5 min. After centrifugation, pour out the supernatant, retain the solid, put the centrifuge tube into a vacuum drying oven, set the pressure to -100 kPa, the temperature to 100 ℃, and the time to 12 h. Grind the dried catalyst again to obtain platinum nitrogen-doped biochar nanomaterials, marked as Pt-NCM.
[0042] A similar method was also used to prepare copper-loaded nitrogen-doped biochar nanomaterials Cu-NCM.
[0043] Figure 1 The X-ray diffraction spectra of the products prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the peak with a 2θ value of about 26° corresponds to the (002) radial plane of carbon. Pt-NCM has obvious diffraction peaks near 39.8°, 46.5°, 67.5°, and 82°. These peaks can be attributed to the (111), (200), (220), and (311) radial planes of platinum, respectively, indicating that platinum nanocrystals have a face-centered cubic structure. CuPt-NCM 3:5 、CuPt-NCM 1:1 、CuPt-NCM 5:3 The positions of the (111) diffraction peaks of the three catalysts shifted significantly to the right compared to the Pt-NCM catalyst, indicating that platinum and copper formed an alloy structure. As the copper content increased, the displacement of the diffraction peak position increased. In addition, it can be seen that the diffraction peak is relatively wide, indicating that the metal particle size is small and the degree of crystallization is low.
[0044] Copper chloride was dissolved in ethylene glycol solution, the pH value was adjusted with sodium hydroxide, and then the copper ions were reduced using microwave heating. Figure 2This is the UV-visible spectrum of copper nanoparticles in ethylene glycol without heating and microwave heating for 50s. It can be found from the figure that before microwave heating, there are three absorption peaks at 201 nm, 231 nm, and 260 nm, and the latter two absorption peaks are relatively small. After heating in a microwave reactor for 50 s, the intensity of the previous three peaks increased, and the positions appeared at 201 nm, 231 nm, and 272 nm, which is very similar to the absorption peak positions (212 nm, 231 nm, and 296 nm) of copper nanoparticles synthesized using various protective agents in other literature. Moreover, at 550 nm, no local surface plasma peak appears, indicating that the particle size of the copper nanocrystal is less than 3 nm. If microwave heating is continued, a small amount of metal precipitation will be seen at the bottom of the round-bottom flask. At this time, the particle size of the metal particles is too large and the crystallinity is too high, which is not the desired result.
[0045] The chloroplatinic acid ethylene glycol solution was heated by microwave, and the UV-visible spectrum was as shown in Figure 3 As shown by Figure 3 It can be seen that when not heated, there are obvious absorption peaks at 200 nm and 268 nm, which can be attributed to Pt (IV). As the heating time increases, the temperature continues to rise, and the intensity of the absorption peak at 268 nm gradually decreases, which means that Pt (IV) is constantly decreasing, while the absorption peak at 220 nm increases, indicating that the amount of divalent metal Pt has increased, indicating that tetravalent Pt is reduced to divalent Pt by ethylene glycol. When the heating time continues to increase, the peak of Pt (II) at 220 nm begins to decrease until it disappears. This shows that as the temperature rises, divalent Pt is converted into atomic Pt. It is worth noting that a weaker absorption peak appears near 250 nm, which may be because the added ethylene glycol is excessive and the atomic platinum forms a complex with a portion of the unoxidized ethylene glycol. Combination Figure 2 and Figure 3 It can be seen that when the heating time reaches 50 s, the copper nanoparticles have crystallized and most of the platinum has been converted into atomic state, but there are still some divalent platinum ions. This shows that the reduction temperature of the two (under the same power and the same heating time, the temperature should be the same) is somewhat different.
[0046] Figure 4 is the infrared spectrum of the platinum-copper sol in Example 1. Obviously, at 1450 cm -1 、1630 cm -1 、1780 cm -1 There are obvious peaks at 3400 cm, which can be attributed to ketones, aldehydes and carboxylic acids, which indirectly indicate that ethylene glycol is oxidized during the reaction with metal ions. -1The adsorption intensity of the stretching vibration peak of hydroxyl group is significantly weakened compared with the infrared spectrum of ethylene glycol, which is also caused by the oxidation of ethylene glycol. -1 There is no obvious peak at the reaction point, which reflects that no CuO is generated during the reaction, further ensuring that the copper ions are fully reduced, which is consistent with the XPS results. By changing the pH value of the ethylene glycol solution, the in-situ generated carboxylate radicals are promoted to act as protective agents and adsorbed onto the particle surface to prevent the metal particles from agglomerating. As a reducing agent, ethylene glycol undergoes an oxidation reaction, with part of it being oxidized to aldehydes or ketones and part of it being oxidized to carboxylic acids.
[0047] Figure 5 The left side shows Pt-NCM (a), CuPt-NCM 3:5 (b) CuPt-NCM 1:1 (c) CuPt-NCM 5:3 (d) SEM images of the four catalysts magnified 50,000 times. The bright part in the image is the metal nanoparticle. From the SEM image, it can be found that as the amount of copper precursor added increases, the proportion of the bright part gradually increases, which indicates that the metal content is increasing, because more copper ions are reduced to atomic state. Moreover, from Figure 5 It was also found that Pt-NCM (a), CuPt-NCM 3:5 (b) CuPt-NCM 1:1 (c) The metal nanoparticles of the three catalysts are dispersed more evenly, while CuPt-NCM 5:3 The metal particles in (d) are agglomerated, which is consistent with the analysis results of HRTEM.
[0048] Figure 5 The four figures on the right correspond to Pt-NCM (a), CuPt-NCM 3:5 (b) CuPt-NCM 1:1 (c) CuPt-NCM 5:3 (d) EDX spectra of the four catalysts. The analysis results are shown in Table 1. At the same time, the N element was detected in the mapping diagram. CuPt-NCM 3:5 (b) CuPt-NCM 1:1 (c) CuPt-NCM 5:3 (d) The weight ratios of copper and platinum in the three catalysts are close to 3:5, 1:1, and 5:3, which is consistent with the assumption. In the XPS analysis results, the atomic ratios of the two metals copper and platinum are consistent with the previously added amounts.
[0049] Table 1 EDX analysis results of four catalysts
[0050] Figure 6 CuPt-NCM 3:5 The mapping diagram of C, O, N, Pt and Cu elements of the catalyst and the SEM photo magnified 10,000 times. It can be seen from the figure that the C element has the highest content, followed by the O element. Pt and Cu elements were also detected in the figure, and the Cu element was slightly more than the Pt element, which is consistent with the EDX analysis results. It can also be seen that the nano-alloy particles of platinum and copper are evenly dispersed on the surface of the nitrogen-doped biochar nanopowder, which is consistent with the TEM analysis results.
[0051] Figure 7 Pt-NCM, CuPt-NCM 3:5 、CuPt-NCM 1:1 、CuPt-NCM 5:3 The full spectrum of the X-ray photoelectron spectra of the four catalysts. The peaks near 285 eV, 533 eV, and 400 eV can be attributed to the C element, O element, and N element, respectively, indicating that after the mixed acid treatment and ammonia treatment, the biochar nanopowder was successfully loaded with O and N elements. In addition, the scanning peaks of Pt4f and Cu2p can also be clearly seen, indicating that metal Pt and Cu were successfully loaded on the nitrogen-doped biochar nanopowder.
[0052] In the XPS spectra of the four catalysts, no characteristic peaks of Cl element were found, which indicates that there are no compounds related to Cl and Cl element has been removed during the washing process. 5:3 There is an obvious peak near 1071 eV, which may belong to the Na element.
[0053] from Figure 7 It can also be seen that with the increase in the amount of copper chloride added, the peaks of the O element (near 500 eV) of the four catalysts show an increasing trend, indicating that metal oxides are inevitably generated during the catalyst preparation process, which may be PtO, Cu2O, etc. Table 2 shows the atomic percentage of each element in each product.
[0054] Table 2 Atomic ratio of each catalyst metal and atomic percentage of each element
[0055] Figure 8 The sample CuPt-NCM is given 3:5XPS spectrum of C, O, and N after separation. From the C1s spectrum, it can be seen that the peaks at 284.51 eV, 285.46 eV, 286.86 eV, and 289.86 eV are attributed to CC, C=C, CO, and C=O, respectively. In the O1s spectrum, 531.8 eV and 533.4 eV are attributed to C=O and CO, respectively. The results of the above two figures show that after mixed acid treatment, a large number of oxygen-containing functional groups are generated on the surface of CNM, which is consistent with expectations. Oxygen functionalization of CNM is a necessary condition for nitrogen doping. From the N1s spectrum, it can be seen that the sample has successfully introduced the N element. There are mainly two functional groups on the surface of NCM: pyridine (399eV) and pyrrole (400.1eV). According to the strength of the peak, it is found that the number of N-containing functional groups in the samples is from most to least: pyrrole and pyridine.
[0056] Fig. 9 The XPS spectra of Pt4f and Cu2p of four catalysts. The peaks near 71.5 eV, 72.8 eV, 75.2 eV, and 77.4 eV in the Pt4f spectrum can be attributed to atomic Pt, PtO, and PtO2. The peaks near 932.6 eV in Cu2p 3 / 2 The peak can be attributed to atomic Cu, indicating that metallic Cu has been successfully loaded in the sample. It can also be seen that there is a relatively small peak near 952.3 eV, which is attributed to Cu2O, indicating that some metallic copper precursor ions have not been completely reduced. Moreover, as the initial amount of copper chloride added increases, the content of oxides also increases. Of course, the peak near 932.6 eV is higher, indicating that most of the Cu is converted into atomic state. It is worth noting that at 940 eV, there is no obvious peak in the Cu2p spectrum, indicating that CuO does not exist in the sample.
[0057] Fig.10 High-resolution transmission electron microscopy images of four catalysts, Pt-NCM (a), CuPt-NCM (b), 3:5 (b) CuPt-NCM 1:1 (c) CuPt-NCM 5:3 (d) In the high-resolution transmission electron micrograph, the lattice fringes of the alloy are marked.
[0058] Fig.11 The particle size distribution diagram of the metal particles of the four catalysts. Pt-NCM (a), CuPt-NCM 3:5 (b) CuPt-NCM 1:1 (c) CuPt-NCM 5:3(d) The average metal particle sizes of the four catalysts are 1.56 nm, 3.34 nm, 3.41 nm, and 12.4 nm, respectively. Obviously, with the increase in the amount of copper added, the formed metal nanoparticles tend to increase in size, and there is a partial agglomeration phenomenon. This may be related to the fact that the Cu nucleation process promotes the Pt nucleation process. In addition, the particle size distribution range also increases in this order. The metal particle size and size distribution of the four catalysts are shown in Table 3.
[0059] Table 3 Metal particle size and size distribution of four catalysts
[0060] 2. Analysis of catalytic activity of redox reaction Linear voltammetry (LSV) and cyclic voltammetry (CV) were used to study and analyze the oxygen reduction reaction activity of the prepared materials. At the same time, the oxygen reduction reaction performance of commercial Pt / C catalysts under the same conditions was also tested and compared with the performance of the catalyst prepared by ourselves. In terms of catalyst loading rate, the prepared Pt-NCM and CuPt-NCM 3:5 、CuPt-NCM 1:1 、CuPt-NCM 5:3 The metal loading rate is 25 wt%, while the loading rate of commercial Pt / C is 40 wt%, and the Pt loading on the rotating disk electrode is 20 ug / cm 2 and 15 ug / cm 2 .
[0061] like Fig.12 As shown, they are Pt / C (a), Pt-NCM (b), CuPt-NCM 3:5 (c) CuPt-NCM 1:1 (d) CuPt-NCM 5:3 (e) Cyclic voltammograms of the four catalysts after 20 activation cycles, with an activation scan rate of 100 mV / s and room temperature. In the range of 0.05-0.35 V, there are strong hydrogen adsorption and desorption peaks, which indicates the presence of platinum atoms on the catalyst surface. At around 0.82 V, all catalysts have a peak related to oxygen reduction, and the oxygen reduction peak of the Pt / C catalyst is sharp and convex. For the remaining catalysts, the peaks tend to become wider with the increase of the amount of Cu, which may be related to the platinum-copper alloy structure. In addition, it can be found that CuPt-NCM 3:5 (c) CuPt-NCM 1:1 (d) CuPt-NCM 5:3(e) There is a broad current peak between 0.6 and 0.9 V for the three catalysts, which indicates that Cu is oxidatively dissolved from the surface of the Pt-Cu alloy structure.
[0062] Fig.13 The CuPt-NCM of the first and 20th cycles are shown 1:1 The cyclic voltammetry curve of the sample clearly shows that in the first cycle, there is an obvious peak at 0.6-0.9 V, which is the oxidation and dissolution of Cu from the surface of the platinum-copper alloy. During the cycle, the intensity of this peak gradually decreases, and after 20 times, it tends to be flat, indicating that Cu on the surface of the platinum-copper alloy structure is almost non-existent, forming a Pt-rich surface. It is worth noting that there is a hydrogen adsorption and desorption peak in the first cycle, indicating that there is a certain amount of Pt on the outer surface of the alloy structure.
[0063] Fig.14 CuPt-NCM 3:5 From the cyclic voltammetry curves of the catalyst at different scan rates, it can be clearly seen that as the scan rate decreases, the hydrogen adsorption / desorption peak area of the curve decreases accordingly.
[0064] Fig.15 Pt-NCM and CuPt-NCM prepared for this experiment 3:5 、CuPt-NCM 1:1 、CuPt-NCM 5:3 Catalyst, as well as the linear sweep voltammetry (LSV) curve of the commercial Pt / C catalyst in an oxygen-saturated 0.5 mol / L sulfuric acid electrolyte. Theoretically, as the reduction potential increases, the electrochemical activity of the material increases and the catalytic performance improves. It can be seen from the LSV curves of the above five catalysts that in the high potential region, the current density does not change with the increase in rotation speed, indicating that the oxygen reduction reaction in this region is a kinetically controlled process of the electrochemical reaction; in the low potential region, the current density increases with the increase in rotation speed. This is because a higher rotation speed is more conducive to the diffusion of oxygen to the electrode surface and participation in the electrode reaction, which also shows that the oxygen reduction reaction in this region is controlled by the diffusion of oxygen and the electrochemical reaction.
[0065] Fig.16 The linear sweep voltammetry curves of different catalysts in 0.5 mol / L sulfuric acid electrolyte saturated with O2, with a scan rate of 5 mV / s, a rotation speed of 1600 rpm, and room temperature. Compared with commercial Pt / C catalysts, the materials prepared in this experiment have a certain gap in the diffusion limiting current value, but the starting potential is close to that of Pt / C catalysts. Only CuPt-NCM 5:3The initial potential of the catalyst is significantly different from that of the Pt / C catalyst, with a difference of 40 mV between the two. This confirms that the nitrogen-doped biochar-supported platinum-copper catalyst has oxygen reduction reaction (ORR) activity. This activity may be related to the high specific surface area of NCM or to the platinum-copper alloy structure.
[0066] In the diffusion and kinetic mixing control stage, the size of the half-wave potential of the LSV curve can reflect the ORR activity of the material. In the LSV curve of the prepared bimetallic catalyst, the order of the half-wave potential is: CuPt-NCM 3:5 >CuPt-NCM 1:1 >CuPt-NCM 5:3 , which indicates that the ORR activity also decreases in this order. CuPt-NCM 5:3 If the particle size is too large, the catalytic effect will be poor.
[0067] Fig.17 CuPt-NCM 3:5 and Pt / C KL curves. It can be seen from the curves that CuPt-NCM 3:5 The linearity of the catalyst is better, and the parallel correlation between the straight lines is also better than that of the commercial Pt / C catalyst. These properties fully demonstrate that the catalyst has first-order reaction kinetics for O2 concentration. Experimental studies have shown that there may be multiple pathways for oxygen reduction reaction, and the direct generation of water from oxygen is the most ideal pathway. The intermediate products in other pathways will cover the catalyst surface and affect the reaction activity.
[0068] Fig.18 is the calculated electrochemical surface area ECSA of each catalyst. As can be seen from the figure, the Pt / C catalyst has the highest ECSA, reaching 20.7 m 2 / g, followed by Pt-NCM catalyst, which is 19 m 2 / g. The electrochemical surface areas ECSA of the other three bimetallic catalysts are relatively low, 16.2 m 2 / g, 15.7 m 2 / g, 13 m 2 / g.
[0069] Fig.19 is the mass activity of different catalysts at 0.675 V and 0.7 V. CuPt-NCM 3:5 The mass activity of the catalyst is the highest, followed by the Pt / C catalyst. At 0.7 V, CuPt-NCM 3:5The mass activity of the catalyst is 1.2 times that of the Pt / C catalyst. The mass activity of the Pt-NCM catalyst is the worst. The mass activities of the other two catalysts with higher copper contents are slightly lower than those of the Pt / C catalyst. The specific order of mass activity of the bimetallic catalysts CuPt-NCM 3:5 >CuPt-NCM 1:1 >CuPt-NCM 5:3 .
[0070] Fig. 20 The Tafel curves and kinetic activity comparisons of different catalysts. The ECSA normalized current density is used as the horizontal axis. The larger the kinetic current density, the smaller the overpotential and the faster the reaction rate, indicating that the electrode electrocatalytic activity is higher. In the range of 0.6-0.72 V, CuPt-NCM has a higher electrocatalytic activity than other catalysts. 3:5 The CuPt-NCM catalyst showed higher kinetic activity, followed by the Pt / C catalyst. 1:1 Table 4 summarizes the catalytic activity data of all catalysts.
[0071] Table 4 Electrocatalytic activity data of all catalysts for oxygen reduction reaction
Claims
1. A method for preparing copper-platinum bimetallic nitrogen-doped biochar nanomaterials, characterized in that The steps include: Step S1: reacting biochar nanomaterials with sulfuric acid and nitric acid to obtain oxygen-functionalized nanopowders, and then calcining the oxygen-functionalized nanopowders at 400° C. in an ammonia atmosphere to obtain nitrogen-doped nanopowders; Step S2: dissolving chloroplatinic acid and cupric chloride in ethylene glycol to obtain a first solution, wherein the molar ratio of copper to platinum is 5:3 to 3:5; dissolving alkali metal hydroxide in ethylene glycol to obtain a second solution; mixing the first solution and the second solution and heating them in a microwave under an inert atmosphere for 1 minute to obtain a copper-platinum sol, wherein the microwave power is 1000 W; Step S3: dissolving the copper-platinum sol in ethanol, and then adding the nitrogen-doped nanopowder in an amount that ensures that the theoretical loading rate of copper-platinum in the nitrogen-doped nanopowder is 20-25%, and then adding nitric acid, standing by ultrasound, and then centrifuging to obtain a solid, and drying and grinding the solid to obtain a copper-platinum bimetallic nitrogen-doped biochar nanomaterial.
2. The method for preparing copper-platinum bimetallic nitrogen-doped biochar nanomaterial according to claim 1, characterized in that: The concentration of chloroplatinic acid in the first solution is 0.01-1.0 g / mL.
3. The method for preparing copper-platinum bimetallic nitrogen-doped biochar nanotubes according to claim 1, characterized in that: The alkali metal hydroxide is sodium hydroxide or potassium hydroxide.
4. The method for preparing copper-platinum bimetallic nitrogen-doped biochar nanotubes according to claim 1, characterized in that: The biochar nanomaterial is prepared by the following method: The corn stalks are crushed into 80-100 meshes, sieved, and placed in an oven for drying at 80° C. for 24 hours; the dried stalk particles are carbonized at 800° C. for 3 hours under N2 protection to obtain the biochar nanomaterial.
5. A bimetallic nitrogen-doped biochar nanomaterial, characterized in that It is prepared by the preparation method described in claim 1, 2 or 3.